The Protective Effect of Ethyl Acetate Fraction and Bioactive Compounds of Mimosa pudica L. Leaves in Methylglyoxal-induced Glucotoxicity - Lan, Pham Thi; Thi Nguyet Hang, Pham; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 1DO - 10.25073/2588-1132/vnumps.4576, 2024)
Mimosa pudica L. has been used as a traditional medicine to treat leprosy, dysentery, burning sensation, asthma, inflammation, fatigue, and blood diseases. This study aimed to evaluate the ethyl acetate (EtOAc) fraction and protocatechuic acid and syringic acid of Mimosa pudica L. leaves against methylglyoxal (MGO)- induced glucotoxicity. The inhibitory effects of EtOAc fraction and two compounds of Mimosa pudica L. on glucotoxicity in Human umbilical vein endothelial cells (HUVECs) and inhibit Advanced glycation end products (AGEs) formation and also breaking effects on MGO-AGEs were measured. Our results demonstrated that EtOAc fraction and protocatechuic acid and syringic acid of Mimosa pudica L. leaves inhibit MGO-induced AGEs formation and break down MGO-AGEs, thus reducing glucotoxicity. EtOAc fraction and two bioactive compounds protocatechuic acid and syringic acid are promised to be effective in preventing or treating MGO-induced endothelial dysfunction.